Work productivity loss among rheumatoid arthritis patients in India: a qualitative study - Jain, Avinash (Rheumatol Adv Pract, 2019)
OBJECTIVE: The aim was to explore the extent to which RA impacts work productivity in patients living with RA in India. METHODS: Face-to-face semi-structured interviews took place with 13 male and seven female patients attending outpatient clinics at Sanjay Gandhi Postgraduate Institute of Medical Sciences, India, living with RA. Patients who were currently working were recruited. Data were audio recorded, transcribed by an independent translation company and analysed using the framework method of thematic analysis. RESULTS: Four themes that explained patients’ experiences of coping with work whilst having RA were identified. These were as follows: balancing act of work and RA, in which participants expressed their day-to-day struggle of living with RA and coping at work; workplace adaptation after RA, in which participants shared insights into communicating with employers and their efforts to adapt at the workplace; support from others and information to manage RA and work, in which participants considered seeking support from different sources that would help them cope at work and understand RA; and wanting a better support mechanism, in which participants made recommendations that could help them to cope at work. CONCLUSION: This is the first study to explore the impact of RA on patients’ work productivity in India. Patients might have different support needs compared with previous studies in other countries. Patients seem to be adopting additional coping strategies not addressed by current interventions or country systems, which might not be sufficient to support patients in remaining employed. Patients made future recommendations.